CHARACTERISTICS OF AIRBORNE INTERFEROMETRIC SYNTHETIC APERTURE RADAR WITH SECTOR SCAN - E. E. Nechayev; K. S. Deryabin (Научный вестник МГТУ ГА)
One of the drawbacks of airborne interferometric synthetic aperture radar is a relatively narrow swath compared to analogous space based systems. Increasing the swath with side view of the interferometer can be possible by increasing the flight altitude and angle of sight. At the same time the height measurement accuracy decreases due to slant range distance increase. Another possible way of swath increasing is using sector scan. The efficiency of sector scan using in interferometric synthetic aperture radar is analyzed in this paper. The mathematical model and geometry of height measurement at a sector scan have been discussed. There was made an analysis of the effect of terrain height and observation angle on received signal phase changing. Observation angle changing is shown to contribute to the phase changing. Potential height accuracy measurement was calculated. The calculation results show that increasing the observation angle reduces height accuracy measurement. The maximum accuracy decrease is obtained at the observation angle of 90°. Despite height accuracy measurement decrease applying the sector scan allow to expand the swath. The accuracy decrease can be limited by selecting optimal parameters of scanning.